2004
DOI: 10.1038/nrn1521
|View full text |Cite
|
Sign up to set email alerts
|

Using human brain lesions to infer function: a relic from a past era in the fMRI age?

Abstract: Recent technological advances, such as functional imaging techniques, allow neuroscientists to measure and localize brain activity in healthy individuals. These techniques avoid many of the limitations of the traditional method for inferring brain function, which relies on examining patients with brain lesions. This has fueled the zeitgeist that the classical lesion method is an inferior and perhaps obsolescent technique. However, although the lesion method has important weaknesses, we argue that it complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
488
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 611 publications
(503 citation statements)
references
References 53 publications
4
488
1
1
Order By: Relevance
“…In addition to intrinsic limitations of lesion mapping studies (Rorden, Fridriksson, & Karnath, 2009;Rorden & Karnath, 2004), part of the aforementioned differences between studies may be attributed to different sample sizes and selection criteria, including criteria for diagnosis, subtype of anosognosia, age, lesion size, perfusion patterns, white matter involvement, and the time interval since stroke for both diagnosis and neuroimaging examination (Karnath et al, 2005;Kortte et al, 2015;Vocat et al, 2010). Unfortunately, addressing all these limitations in a single study is currently unfeasible for most labs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to intrinsic limitations of lesion mapping studies (Rorden, Fridriksson, & Karnath, 2009;Rorden & Karnath, 2004), part of the aforementioned differences between studies may be attributed to different sample sizes and selection criteria, including criteria for diagnosis, subtype of anosognosia, age, lesion size, perfusion patterns, white matter involvement, and the time interval since stroke for both diagnosis and neuroimaging examination (Karnath et al, 2005;Kortte et al, 2015;Vocat et al, 2010). Unfortunately, addressing all these limitations in a single study is currently unfeasible for most labs.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the conflicting results of previous studies, as well as the frequent co-occurrence of AHP and DSO, warrant a specific examination of the relation between DSO and AHP. In the current study we used a voxelbased, lesion comparison approach (Kimberg, Coslett, & Schwartz, 2007;Rorden & Karnath, 2004;Rorden, Karnath, & Bonilha, 2007) to test the hypothesis that at least partially segregated networks are damaged in AHP and DSO, involving more cortical premotor and insular grey matter areas in the former, and subcortical white and grey matter structures (basal ganglia and white matter tracts around them) in the latter. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 Based on these assessments, patients were categorized into four different groups: 1.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral measures are treated dichotomously when the hypothesis is that a region is critical for normal function. In related work, Karnath, Rorden and colleagues (Karnath et al, 2004;Rorden and Karnath, 2004) recently demonstrated voxelwise chi-square tests for the significant association of lesion and deficit. They also developed Voxel-based Analysis of Lesions (VAL) for analyzing dichotomized behavioral and lesion measures while covarying for lesion size or other covariates with logistic regression.…”
Section: Discussionmentioning
confidence: 99%
“…The same alpha threshold was used in the logistic regression in Karnath et al (2004). It is important to acknowledge that the method proposed here does not include a suitable solution to correct for the problem of multiple comparisons that result from multiple voxel analysis.…”
Section: General Statistical Issuesmentioning
confidence: 99%
See 1 more Smart Citation